The Moral Vacuum in Teacher Education Research and Practice. Issue 13 (December 2013) - Sanger, Matthew; Osguthorpe, Richard
This chapter examines the gap between the widespread acknowledgment that teaching is a moral endeavor, on the one hand, and the lack of explicit, systematic teacher education research and practice to support preparing teachers for the moral aspects of teaching. After providing an initial description of the aforementioned gap, the chapter surveys the evidence that such a gap exists, then takes up a number of themes found in the literature bordering the gap. It concludes with a discussion of possible paths for teacher education research and practice to move forward. Teachers do not lack moral sophistication because they are not moral people. Just the opposite, most teachers are drawn to teaching because of their moral commitments. Moral language is missing in classrooms, but it is also missing in the seminar rooms and lecture halls of teacher education. (Sockett & LePage, 2002, p. 171)